ANALISIS PROGRAM MARKET DAY SEBAGAI UPAYA MENUMBUHKAN NILAI KEWIRAUSAHAAN SISWA SDIT AL-BINA PANGKALPINANG - Ariska; Diana Pramesti; Rifki Hanif Setiawan (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
Market Day is an activity where students sell merchandise that has been made and then offered to other students, teachers and employees at the school. Every week, on Friday at SDIT Al-Bina Pangkalpinang, all classes take turns implementing the Market Day program. Market Day activities are one of the entrepreneurship education that seeks to foster students' entrepreneurial values ​​from an early age, especially student independence. Therefore, researchers are interested in studying and further researching the efforts made by schools in fostering entrepreneurial values ​​in SDIT Al-Bina Pangkalpinang students and the obstacles in its implementation.This type of research uses descriptive qualitative research methods. Data is collected through interviews, observation, and documentation. Data analysis uses the Miles and Huberman model of qualitative descriptive analysis. Activities in data analysis include data reduction, data display, and conclusion drawing/verification. The validity of the data is checked using triangulation techniques and sources. The results of research at SDIT Al-Bina Pangkalpinang, namely the Market Day program at SDIT Al-Bina Pangkalpinang, have been successful in fostering entrepreneurial values ​​in students through regular hands-on activities every Friday by involving all students in economic activities which include production, distribution and consumption activities. The entrepreneurial values developed in students are independence, creativity, courage to take risks, action orientation, leadership and hard work. In implementing Market Day activities at SDIT Al-Bina Pangkalpinang there were obstacles, but they did not become a barrier for the school to implement it.